Corporate Social Responsibility and Community Welfare: A Critical Perspective through the Lens of Maslahah - Sanda, Juana Tria; Nurlaila, Nurlaila; Silalahi, Purnama Ramadani (Tasharruf: Journal Economics and Business of Islam, 2025)
This study analyzes the optimization of Corporate Social Responsibility (CSR) at PT Socfin Indonesia (Socfindo) and its relevance to the review of maslahah in improving community welfare. A research gap was identified from the striking difference between the company's broad claims about its CSR (based on the 2018-2024 sustainability report) and the critical perceptions of the community, which highlight fundamental issues such as agrarian conflicts and factory waste management. Using a qualitative approach with a single case study design and interview techniques (n=3 informants), this study analyzes the implementation of Stakeholder Theory. The findings show a tendency for the company to be reactive rather than proactive in responding to core stakeholder issues. Analytically, although PT Socfin Indonesia's CSR programs have the potential to bring about maslahah (benefits), the existence of mafsadah (harm/danger) caused by the company's core operations hinders the achievement of holistic welfare. The significant contribution of this research lies in the integration of the concept of maslahah as a critical analytical lens to evaluate the impact of CSR more comprehensively, beyond a purely normative framework. The research results underscore the urgency of a more participatory and proactive CSR approach in resolving root causes. The limitations of the study include the specific scope of informants in a single case, limiting direct generalization.